Dinamika Alih Fungsi Lahan Sawah dan Upaya Perlindungan Lahan Pertanian Pangan Berkelanjutan di Wilayah Metropolitan Sarbagita - Ramadhan, Syahri; Murti, Ratna Patmawati Wisnu (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2024)
The urbanization phenomenon has a positive impact on economic development, but it also has a negative impact on land conversion in the Sarbagita Metropolitan area. This research is a descriptive study that aims to identify changes in the function of paddy fields from 2018 to 2023, as well as local government steps in protecting sustainable food agricultural land (LP2B). The results of the analysis show that paddy fields have shrunk between 3-6% of the total area of the district/city. The conversion of agricultural land occurs in tourism areas such as Denpasar City and Badung Regency, as well as in city centers such as Gianyar Regency and Tabanan Regency. LP2B protection is an integral part of regional spatial planning through the establishment of spatial pattern plans. The local government in the Sarbagita Metropolitan Area has established several policies to protect LP2B. Permits ensure that land use aligns with the prepared spatial pattern plan. The integration of detailed spatial planning plans (RDTR) into the Online Single Submission (OSS) system creates synergy between spatial planning and permit processes, thereby achieving efficiency, transparency, and more effective coordination between government agencies. Fenomena urbanisasi berdampak positif pada peningkatan ekonomi tetapi juga berdampak negatif pada alih fungsi lahan di wilayah Metropolitan Sarbagita. Penelitian ini merupakan penelitian deskriptif yang bertujuan untuk mengidentifikasi alih fungsi lahan sawah dari tahun 2018 hingga 2023 serta langkah pemerintah daerah dalam melindungi lahan pertanian pangan berkelanjutan (LP2B). Hasil analisis menunjukkan bahwa lahan sawah menyusut antara 3-6% dari total luas wilayah kabupaten/kota. Alih fungsi lahan pertanian terjadi di kawasan pariwisata seperti Kota Denpasar dan Kabupaten Badung, serta di pusat kota seperti Kabupaten Gianyar dan Kabupaten Tabanan. Perlindungan LP2B menjadi bagian yang tidak terpisahkan dalam penataan ruang wilayah melalui penetapan rencana pola ruang. Pemerintah daerah di wilayah Metropolitan Sarbagita telah menetapkan beberapa kebijakan untuk melindungi LP2B. Pengendalian pemanfaatan ruang dilakukan melalui perizinan guna memastikan penggunaan lahan sesuai dengan rencana pola ruang yang telah disusun. Integrasi rencana detail tata ruang (RDTR) ke dalam sistem Online Single Submission (OSS) menciptakan sinergi antara perencanaan tata ruang dan proses perizinan, sehingga tercapai efisiensi, transparansi, dan koordinasi antar lembaga pemerintah yang lebih efektif.